2007
DOI: 10.1039/b704539e
|View full text |Cite
|
Sign up to set email alerts
|

A study on the photodynamic properties of chlorophyll derivatives using human hepatocellular carcinoma cells

Abstract: Photodynamic therapy (PDT) is an alternative anticancer treatment in which direct tumor-cell killing results from selective accumulation of photosensitizers in the tumor sites and phototoxicity occurs when light-activated photosensitizers transfer the energy to oxygen nearby to produce singlet oxygen. The objective of this study was to investigate the effects of PDT using chlorophyll derivatives such as pheophytin a (phe a), pheophytin b (phe b), pheophorbide a (pho a) and pheophorbide b (pho b) as the photose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 35 publications
0
44
0
3
Order By: Relevance
“…PDT was reported to inhibit cancers through different cell death pathways and its effectiveness is dependent on the types of cancer cell lines and photosensitizers (Buytaert et al, 2007;Zuluaga and Lange, 2008). Previous studies on the potential of Pa as a photosensitizer have suggested that Pa is effective to inhibit cancer growth by the induction of apoptosis (Inanami et al, 1999;Hajri et al, 1999;Hajri et al, 2002;Lee et al, 2004;Lim et al, 2004;Tang et al, 2006;Li et al, 2007;Radestock et al, 2007;Kishino et al, 2008;Rapozzi et al, 2009;Tang et al, in press-a,b). We speculated that the apoptosis is a general anti-tumor mechanism of Pa-PDT on human cancers.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…PDT was reported to inhibit cancers through different cell death pathways and its effectiveness is dependent on the types of cancer cell lines and photosensitizers (Buytaert et al, 2007;Zuluaga and Lange, 2008). Previous studies on the potential of Pa as a photosensitizer have suggested that Pa is effective to inhibit cancer growth by the induction of apoptosis (Inanami et al, 1999;Hajri et al, 1999;Hajri et al, 2002;Lee et al, 2004;Lim et al, 2004;Tang et al, 2006;Li et al, 2007;Radestock et al, 2007;Kishino et al, 2008;Rapozzi et al, 2009;Tang et al, in press-a,b). We speculated that the apoptosis is a general anti-tumor mechanism of Pa-PDT on human cancers.…”
Section: Discussionmentioning
confidence: 91%
“…Pa has been commercial available as it can be purified from a number of traditional medicine sources such as Scutellaria barbata, Psychotria acuminata, as well as silkworm excreta (Glinski et al, 1995;Lim et al, 2002;Chan et al, 2006). Previous studies have suggested that the therapeutic potential of Pa-mediated photodynamic therapy (Pa-PDT) on leukaemia, pigmented melanoma, colonic cancer, hepatoma and uterine carcinosarcoma (Hajri et al, 2002;Lee et al, 2004;Lim et al, 2004;Tang et al, 2006;Li et al, 2007;Tang et al, in press-a).…”
Section: Introductionmentioning
confidence: 95%
“…Pba was shown to cause mitochondria-dependent apoptosis in cultured cancer cells (Tang et al, 2009). In vivo animal models also demonstrated that Pba impedes tumor growth in colon carcinoma and hepatoma xenograft models (Hajri et al, 2002;Li et al, 2007). However, the development of PDT resistance has been displayed: colon cancer cells repeatedly exposed to PDT agents developed resistance to PDT (Singh et al, 2001).…”
Section: Orgmentioning
confidence: 99%
“…Investigation on the MeOH extract of the plants has led to the isolation of 14 compounds, four steroids: 5α, 8α-epidioxy-(24ξ)-ergosta-6,22-dien-3β-ol (1) (Figure 1) [3], β-sitosterol (2) (Figure 2) [4], β-sitostenone (3) (Figure 3) and stigmastenone (4) (Figure 4) [5] ; one terpenoid: lupeol (5) [6]; one glyceride: 1,3-dipalmitoyl-2-oleoylglycerol (6) [7]; one alkanoid: linoleic acid (7) [8]; two benzenoids:  methylparabene (8) [9] and isovanillic acid (9) [10]; and five chlorophylls: pheophytin-a (10) [11], pheophorbide a methyl ester (11) [12], methyl-13 2 -hydroxy-(13 enriched with acetone to furnish 10 fractions (1-1 to 1-10). Fraction 1-1 (1.72 g) was re-subjected to Si gel chromatography, eluting with n-hexane/acetone (80:1) to obtain linoleic acid (7) (58 mg, 0.0357%).…”
Section: Introductionmentioning
confidence: 99%